2020
DOI: 10.3823/839
|View full text |Cite
|
Sign up to set email alerts
|

Cefotaxime vs Ceftriaxone for the Management of Preterm Premature Rupture of Membranes

Abstract: Introduction: Antibiotics are well known and recommended as the main therapy for preterm premature rupture of membranes (PPROM.) But the research on antibiotics other than the recommended macrolides regimens is still lacking. This research aims to evaluate whether there are effects differences of cefotaxime and ceftriaxone given on pregnancy with PPROM by comparing the duration of the latency period and the infants outcomes. Material and Methods: Data was taken retrospectively through medical records at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Both antibiotics have been proven to delay preterm labor in patients with premature rupture of membranes. (Rasti et al, 2020)…”
Section: Probioticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both antibiotics have been proven to delay preterm labor in patients with premature rupture of membranes. (Rasti et al, 2020)…”
Section: Probioticsmentioning
confidence: 99%
“…Rasti et al chose these two antibiotics because they have lower side effects, minimal risk of allergies, are safe to use during pregnancy, and are more sensitive in treating bacterial infections in PROM, namely: Staphylococcus, Streptococcus dan Escherichia coli. (Rasti et al, 2020) Vaginal infections are significantly reduced with the help of probiotic therapy during pregnancy. Observational research by Kavak et al in 2014 reported that the addition of probiotics with the antibiotic ampicillin in preterm PROM patients was able to delay labor for 5 days and prevent infection.…”
mentioning
confidence: 99%